Using information technology a practical introduction to computers & communications - Williams, Brian K. (McGraw-Hill/Irwin, 2003)
This text covers the fundamental computing concepts that are part of the digital age, including software, hardware, data, people and procedures. It seeks to educate the technology consumer, using themes of ethics, the Internet and communications to demonstrate how technology influences our lives